Crude - Berlinger, Joe (New York, NY : First Run Features, 2010)
Documents the lawsuit brought against Chevron by thousands of Ecudorean natives over contamination of water in the Ecuadorean Amazon rainforest.
Originally released as a motion picture in 2009.
Features: audio commentary by Joe Berlinger, inteview with Berlinger & Trudie Styler, bonus scenes, My Sundance premiere, photo gallery.
DVD.
In English and Spanish with English subtitles.
Keywords: Chevron Oil Company; Petroleum industry and trade -- Amazon River Region; Oil spills -- Environmental aspects -- Amazon River Region; Actions and defenses -- Ecuador; Documentary films; Nonfiction films; Feature films